Parent-child separation and cardiometabolic outcomes and risk factors in adulthood: A systematic review - Tang, Alva; Ertel, Karen A.; Keen, Ryan; Beyer, Logan; Eckert, Natalie; Mita, Carol; Pintro, Kedie; Okuzono, Sakurako S.; Yazawa, Aki; Slopen, Natalie (Psychoneuroendocrinology, 2023)
Parent-child separation has been associated with negative mental health across childhood and adulthood, yet little is known about the long-term impacts for cardiovascular health. This systematic review synthesized and evaluated the quality of the literature examining the association between exposures to parent-child separation and cardiometabolic outcomes in adulthood. Following a registered protocol, online databases (Pubmed, PsycInfo, and Web of Science) were searched for relevant studies. Studies were included if they (a) defined the exposure before age 18 as institutionalization, foster care placement, parental incarceration, separation due to parents migrating for economic reasons, or asylum and war; and (b) quantified the association between parent-child separation and cardiometabolic events and diagnoses (e.g., coronary heart disease, diabetes) and risk factors (e.g., body mass index, fat distribution, serum-based metabolic markers, inflammatory markers in adulthood (≥ age 18). Studies lacking an unexposed comparison group were excluded. The risk for bias in each study was assessed with a modified Newcastle-Ottawa Scale. Of the 1938 studies identified, 13 met our inclusion criteria. Two of the four studies examining associations between parent-child separation and cardiometabolic events and diagnoses found positive associations with coronary heart disease and diabetes. Amongst the 13 studies examining associations with any type of adult cardiometabolic risk factors, eight studies reported at least one positive association. Sub-analyses considering separate reasons for parent-child separation provided clearer insights: War evacuation was associated with hypertension and high blood pressure across four studies from the same cohort; out-of home care experiences largely evidenced null results across five different studies, and two studies on parental incarceration suggested positive associations with elevated inflammation, BMI and blood pressure. The connections between parent-child separation and adult cardiometabolic outcomes and risk factors are currently inconsistent. The results may depend on the reason for separation, age of assessment, analytic differences and other psychosocial variables that are often unmeasured in this literature. •Parent-child separation is associated with poor psychosocial functioning and health behaviors, but little is known which about cardiometabolic health.•Our review finds that the extant evidence show inconsistent associations between parent-child separation and adult cardiometabolic outcomes .•More high-quality research is needed to substantiate its effects on cardiometabolic health and mechanisms.